2017
DOI: 10.1136/bmjopen-2016-015809
|View full text |Cite
|
Sign up to set email alerts
|

Usage of ambulance transport and influencing factors in acute coronary syndrome: a cross-sectional study at a tertiary centre in China

Abstract: ObjectivesThe aim of this study was to explore the choice of transportation mode to hospital in patients with acute coronary syndrome (ACS) and to determine the factors influencing the use of ambulance.Design, setting and participantsThis cross-sectional study was conducted in a tertiary and teaching hospital in China. The study was carried out between 24 August 2015 and 24 July 2016. A total of 828 patients with ACS presented at the emergency department (ED) were included. The study population was dichotomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 30 publications
2
27
1
2
Order By: Relevance
“…However, the data presented here showed that direct visits to PCI centres (28%) or transfers from non-PCI centres (50.3%) were more frequent, and utilisation of EMS (21.7%) was less frequent than that seen in previous studies conducted in Western countries [29,34,35]. Despite frequencies similar to those of other Asian countries [36,37], a significant need to identify predictors of non-utilisation of EMS among STEMI patients remains. Although certain clinical variables have been linked to non-use of EMS services, these results remain controversial [36][37][38][39].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, the data presented here showed that direct visits to PCI centres (28%) or transfers from non-PCI centres (50.3%) were more frequent, and utilisation of EMS (21.7%) was less frequent than that seen in previous studies conducted in Western countries [29,34,35]. Despite frequencies similar to those of other Asian countries [36,37], a significant need to identify predictors of non-utilisation of EMS among STEMI patients remains. Although certain clinical variables have been linked to non-use of EMS services, these results remain controversial [36][37][38][39].…”
Section: Discussioncontrasting
confidence: 57%
“…Despite frequencies similar to those of other Asian countries [36,37], a significant need to identify predictors of non-utilisation of EMS among STEMI patients remains. Although certain clinical variables have been linked to non-use of EMS services, these results remain controversial [36][37][38][39]. In accordance with other studies, old age was not shown to be an independent factor for non-utilisation of EMS.…”
Section: Discussionmentioning
confidence: 95%
“…This contributes to significant delays in PCI [ 12 ]. Low rates of ambulance utilisation in myocardial infarction have also been described in China [ 15 ], Ireland [ 16 ], and the United States [ 17 ]. For this reason, public education campaigns should highlight the importance of ambulance transport.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, we found that the more severe the symptoms of STEMI were, the higher was the rate of EMS use. 24 Some studies have evaluated the association between EMS use and past medical history. 11,24 This study showed that patients with STEMI who had a history of coronary artery disease were much more likely to use EMS (odds ratio, 2.47) compared to those without a history of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%